Expression and Characterization of Carotenoid Cleavage Oxygenases From Herbaspirillum seropedicae and Rhodobacteraceae bacterium Capable of Biotransforming Isoeugenol and 4-Vinylguaiacol to Vanillin - Han, Zichun; Long, Liangkun; Ding, Shaojun (Frontiers in Microbiology, 2019)
HsCCO and RbCCO from Herbaspirillum seropedicae and Rhodobacteraceae bacterium were selected and characterized from five putative bacterial carotenoid cleavage oxygenase gene sequences due to their merits in the expression solubility and catalytic properties. Both enzymes can convert 4-vinylguaiacol and isoeugenol to vanillin. HsCCO showed maximum activity at 40 ℃ and pH 7.0 and was stable at pH 6.5-10 and temperature around 25 °C, retaining over 90 % and 80% of initial activity, respectively. RbCCO showed maximum activity at 35 ℃ and pH 9.0 and was stable at pH 6-11 and temperature 25 ℃ to 30 ℃, retaining over 80% of initial activity. The kinetic constants Km of HsCCO for isoeugenol and 4-vinylguaiacol were 1.55 mM and 1.65 mM and Vmax was 74.09 nmol min-1 mg-1 and 27.91 nmol min-1 mg-1, respectively. The kinetic constants Km of RbCCO for isoeugenol and 4-vinylguaiacol were 2.24 mM and 0.85 mM and Vmax was 76.48 nmol min-1 mg-1 and 19.96 nmol min-1 mg-1, respectively. The transformed E. coli cells harboring HsCCO converted isoeugenol and 4-vinylguaiacol at molar conversion yields of 80% and 55% and the maximum vanillin concentrations were up to 1.22 g L-1 and 0.84 g L-1, respectively. Comparably, the molar conversion yields of the transformed E. coli cells harboring RbCCO against isoeugenol 4-vinylguaiacol were 75% and 58%, and the maximum vanillin yields were up to 1.14 g L-1 and 0.88 g L-1, respectively.